Microbial consortia and up-to-date technologies in global soy sauce production: a review - Chong, Shin Yee; Ilham, Zul; Samsudin, Nik Iskandar Putra; Soumaya, Sassi; Wan-Mohtar, Wan Abd Al Qadr Imad (Universiti Putra Malaysia, 2023)
Soy sauce is an Oriental fermented condiment, and key ingredient in many Asian cuisines. As consumers around the world are becoming more adventurous with their eating choices and preferences, the demand for and popularity of Asian cuisines are increasing globally. The underlying basis of soy sauce fermentation is intricate microbial interactions which play a vital role in defining the quality, flavour, and smell of the resulting soy sauce. Traditional soy sauce fermentation consists of a two-step process: koji and moromi fermentation. Despite the presence of beneficial microorganisms in soy sauce, various harmful microorganisms can also be found during the koji or moromi step, thus resulting in soy sauce contamination. Therefore, studying the biodiversity and interactions of microorganisms is critical in ensuring soy sauce quality. The present review thus discusses in depth the various bacterial and fungal species that are either beneficial or harmful to soy sauce fermentation. The present review also discusses the advances in soy sauce fermentation such as the enhancement of gamma-aminobutyric acid (GABA) in soy sauce by microorganisms, the enhancement of soy sauce flavour by mixed starter culture, and by genome shuffling starter culture.